PENGARUH METODE PROBLEM BASED LEARNING DAN PENGGUNAAN BUKU TEKS UNTUK PENINGKATAN KEMAMPUAN KOSA KATA BAHASA INGGRIS BAGI SISWA KELAS VIII DI SMPN 1 GENTENG - Mustofa, Ali; Priawasana, Endra; Kustiyowati, Kustiyowati (IAI Darussalam, 2023)
Mastery of English requires a lot of vocabulary and adequate grammatical forms. A large vocabulary without being based on strong grammar makes it impossible for us to properly understand a reading and vice versa, good grammar without having a vocabulary. To simplify and overcome this, it is necessary to use the Problem Based Learning (PBL) learning model and learning media, Problem In this study, the method used was the Pre-Experimental Design method with the One Group Pretest-Posttest Design research design, where in this design a causal relationship will be revealed by viewing one group of subjects. The data analysis used in this study used descriptive statistics. and inferential statistics. Analysis of data on test results for students' vocabulary comprehension abilities was carried out quantitatively. The statistical test used in this study is the inferential test of the independent t test. Daa analysis using SPSS version 24. The results showed that there was a positive and significant effect of the use of picture story books on the speaking ability and English vocabulary of junior high school students. These results indicate that junior high school students who are taught with picture story books as a medium have an increased speaking ability using English vocabulary compared to before learning.